PENGARUH MODAL SOSIAL TERHADAP PRODUKTIVITAS PETANI SAYURAN ORGANIK DI DESA BATUR, KECAMATAN GETASAN, KABUPATEN SEMARANG - Tambunan, Dyantri E. M. (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2018)
The aims of this study were to determine the effect of social capital on the productivity of organic farmers in the Batur Village, District Getasan, Semarang Regency. This research was conducted in February 2018 to March 2018 at Batur Village, District Getasan, Semarang Regency. Survey was used in this research. The respondents were chosen among organic Farmers in Batur village, District Getasan, Semarang in total. There were 70 respondents in this research. Data were analysed by multiple linear regression analysis. The result of the analysis showed that (1) the variables of network had a significant effect on productivity of organic vegetable farmer; (2) the variables of trust had not a significant effect on productivity of organic vegetable farmer; (3) the variables of participation had a significant effect on productivity of organic vegetable farmer; (4) the variables of norm had a significant effect on productivity of organic vegetable farmer; (5) the variables of network, trust, participation, and social norm had a significant effect on productivity of organic vegetable farmer.